PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMBAR PADA MATERI FUNGI (JAMUR ) TERHADAP MOTIVASI DAN HASIL BELAJAR SISWAKELAS X SMA SWASTA PAB 8 SAENTIS - syahreni tanjung; Khairuddin; Rohani (Jurnal Bionatural, 2024)
Learning methods that are often used in this class. The discovery learning learning model also has an influence on student learning outcomes in the experimental class at SMA PAB 8 Saentis. It can be seen that the average score for students is before the influence of test results, pre-test and post-test in the experimental class and control class, namely the results of the pretest in the experimental class. The score was 2,280, and the average student score was 71.2 with medium criteria, and the posttest score in the experimental class was 2,705 and the average student score was 84.5 with high criteria. Meanwhile, the pretest score from the control class was 2.147 and the average student score was 65.0 with sufficient criteria. And the posttest score in the control class was 2.523, the average student score was 76.4 with medium criteria.